Junction City and the Chisholm Trail - Katie Goerl (Symphony in the Flint Hills, 2017)
Introduction: Oral history tells of a site on the banks of McDowell Creek in northeast Geary (formerly Davis) County called Dead Man’s Gulch. The case was already cold in August 1875 when they first found the body of the dead sheepherder. According to the local newspaper, the cause of death was apparent. Yet a mystery lingered around his death that survived only in rumor and memory, rooted in the history of the rivalry that simmered between farmers and cattlemen. It began with the Chisholm Trail.
Keywords: Kansas; cattle trade; opposition by farmers; herd law; violence